Economic and social vulnerability because of Covid-19: poverty and food security - Cruz Reyes, María Angélica; De Luna Bonilla, Mary Xóchitl; Chávez Ayecac, Vianey (Mercados y Negocios, 2022)
The objective is to analyze food poverty and the effects in terms of vulnerability because of the Covid-19 pandemic in Mexico City from the capability approach. In the analysis stage, centrality, variability, and correlation parameters were used to identify the effects of the health crisis on food poverty. The results corroborate that food poverty is a material and immaterial phenomenon that impacts the individual’s economic, sociocultural, and environmental settings. The State must design strategies with different societal stakeholders for social and economic recovery, not only because of the implications of the pandemic but also because of the economic inequality among the population.